Treatment Trends of Adult Brachial Plexus Injury: A Bibliometric Analysis. Issue 9 (15th September 2021) - Čebron, Urška; Mayer, Johannes A.; Lu, Chao; Daigeler, Adrien; Prahm, Cosima; Kolbenschlag, Jonas
Abstract : Background: Brachial plexus injury is often debilitating because it can severely impair upper extremity function and, thus, quality of life. The surgical treatment of injuries to the brachial plexus is very demanding because it requires a profound understanding of the anatomy and expertise in microsurgery. The aim of this study was to get an overview of the landscape in adult brachial plexus injury surgery, and to understand how this has changed over the years. Methods: The most frequently cited articles in English relevant to adult brachial plexus injury were identified through the Web of Science online database. Results: The average number of citations per article was 32.8 (median 24, range 4–158). Authors from 26 countries contributed to our list, and the US was the biggest contributor. Almost half of all nerve transfer cases were described by Asian authors. Amongst nerve transfer, the spinal accessory nerve was the preferred donor overall, except in Asia, where intercostal nerves were preferred. Distal nerve transfers were described more often than plexo-plexal and extra-plexal-to-plexal transfers. The most common grafts were sural nerve grafts and vascularized ulnar nerve grafts, which became popular in the last decade. Conclusions: Our study sheds light on the regional variations in treatment trends of adult brachial plexus injury, and on the evolution of the field over the last 30 years. The articles included in our analysis are an excellent foundation for those interested in the surgical management of brachial plexus injuries.